EFFECT OF APPLICATION USING FOR HEALTH BEHAVIOR TRACKING ON HEALTH BEHAVIORS, AND HEALTH PSYCHOLOGICAL CAPITAL OF THE WORKING ADULTS AT RISK OF NCDs - Vanno, Vitanya; Seewungkum, Dussadee (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
The number of working adults with non-communicable diseases or NCDs are continuously increase. This is an important health issue leading to illness and premature death of working adults. The objectives of this research were to study the effect of application using for health behavior tracking on health behaviors and health psychological capital of the working adults at risk of NCDs. The participants were 41 working adults at risk of NCDs. These participants were assigned to the experimental group and the control group by simple random sampling. The manipulated variable was the application using/no using and the dependent variables were the NCDs-related health behaviors and the NCDs-related health PsyCap. The instruments were the mobile application for health behavior tracking, the NCDs-Health Behaviors Scale (Alpha = .782), and the NCDs-Health PsyCap Scale (Alpha = .897). The Pretest-Posttest Control Group Design was used in this study. The data were analyzed by using mean, standard deviation, and t-test. Result showed that the score of the NCDs-related health behaviors of working adults was increased after using the application at the statistically significant level of .001. The result also found that the difference in pretest and posttest score for the NCDs-related health behaviors of working adults in the experimental group was significantly higher than those in the control group at the statistically significant level of .01. However, no significant difference was found in the score of the NCDs-related health PsyCap between before and after using the application. Furthermore, no significant difference was found between working adults in the experimental group and the control group on the score of difference in pretest and posttest for the NCDs-related health PsyCap. This research revealed the effectiveness of the application only on the NCDs-related health behaviors. This application should be improved in the part of the NCDs-related health PsyCap enhancement before using in the future.